Diagnosis and behavior in autonomic trigeminal headaches - Erélido Hernández Valero; María Octavina Rodríguez Roque (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Autonomic trigeminal headaches are primary headaches which include: cluster headaches, paroxistical hemicranea, and syndrome of unilateral headache in a neuralgic way, of short duration, accompanied by cojunctival injection and tearing and the continuous hemicranea. It is also accompanied by autonomic manifestations such as: palpebrate ptosis, tearing, nasal congestion, rhinorrhea, Horner syndrome (palpebrate ptosis, miosis, and enophthalmos) and changes in the coloration of the periocular skin and in the cheek. In this paper we propose the most likely diagnosis and therapeutic to this nosologic entity